ChatGPT as a Tool for Language Development: Investigating Its Impact on Proficiency and Self-Evaluation Accuracy in Indonesian Higher Education - Prasetya, Rizky Eka; Syarif, Achmad (Universitas Hamzanwadi, 2023)
English language learning plays a crucial role in today’s globalized world, and the integration of technology, particularly chatbots, has shown promise in enhancing language learning experiences. However, there is a noticeable gap in the literature regarding the application of chatbots in the specific context of Indonesia University. This research employs a mixed-methods approach, combining quantitative and qualitative data collection methods. A sample of 100 students from Indonesia University participated in pre-test and post-test assessments to measure language development. Additionally, the accuracy of students’ self-assessments was evaluated before and after using ChatGPT. The main findings of this study indicate that personalized feedback provided by ChatGPT significantly influenced students’ language development, as evidenced by the notable improvement in post-test scores. Furthermore, there was a considerable increase in self-assessment accuracy after students engaged with ChatGPT, demonstrating the effectiveness of personalized feedback in enhancing students’ ability to evaluate their language proficiency. Participants reported that ChatGPT facilitated language learning by providing interactive feedback and targeted guidance, allowing learners to practice and improve their language skills at their own pace. English language learners perceive benefits such as interactive feedback, increased motivation, and resource accessibility. While challenges exist, the advantages outweigh the limitations. These findings contribute to understanding the potential of chatbots, specifically ChatGPT, as effective language learning tools in self-directed learning environments. This finding offers valuable insights for educators and practitioners in implementing chatbots effectively within language pedagogy, ultimately contributing to more effective and engaging English language learning experiences in the Indonesian university context.